Impact of dose‐finding studies on administration of oxytocin during caesarean section in the UK1. (15th August 2013) - West, R.; West, S.; Simons, R.; McGlennan, A.
Summary Debate continues over the dose and methods of administration of oxytocin for the prevention of haemorrhage during caesarean section. We surveyed 206 lead obstetric anaesthetists in the UK to determine standard practice in their unit as well as any differences in practice for high‐risk cases. There were 150 responses (72.9% response rate). A total of 149 units use oxytocin. The majority use an initial 5‐IU dose, whilst a small proportion (8; 5.3%) administer a dose < 5 IU for elective caesarean section. The administration of a 10‐IU dose has ceased altogether. There is a broad range of administration methods, particularly with infusions. Forty (26.8%) respondents give a different oxytocin regimen following caesarean section in patients with severe pre‐eclampsia, 72 (48.3%) in those with cardiac disease of New York Heart Association class 1‐2, and 100 (66.7%) with class 3‐4. In conclusion, there is a trend towards the use of lower doses of oxytocin in caesarean section, but there are still wide variations in detail. We suggest that there is a need for a national protocol to standardise oxytocin administration.